Pemanfaatan Limbah Plastik sebagai Alternatif Bahan Pelapis (Upholstery) pada Produk Interior - Sofiana, Yunida (Humaniora, 2010)
Environment pollution which is caused by garbage, especially plastic products, is one undeniable thing nowadays. Environment pollution by non-degradable materials could be decreased in 3Rs that are recycling, reusing, reducing. Recycle method is one of creative methods; the plastic waste could be recycled into matting materials that substitute natural material (pandanus) and also to be alternative upholstery in interior products. Plastic waste treatment process until disposable is easier than natural material which has to go through several stages like drying and staining. What could be gained from pandanus could also be gained from plastic waste, so there are many things probable products could be designed. The product image is assumed to be modern, one trend nowadays.